2013
DOI: 10.1212/wnl.0b013e3182a956ad
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Parkinson disease after depression

Abstract: The likelihood of developing PD is greater among patients with depression than patients without depression. Depression may be an independent risk factor for PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
1
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 42 publications
4
77
1
5
Order By: Relevance
“…Our results are consistent with a growing body of evidence for the relationship between depression and subsequent PD, [4][5][6][7][8][9][10][11][12][13][14] and the present study contributes to this evidence with strong, prospective, long-term data. One recent study 13 reported a similar, significant association over a 10-year period, but investigations covering more than a decade of follow-up are rare Table 3 Risk of PD in relation to estimated severity and recurrence of depression, assessed by binary logistic regression and results have been inconclusive.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are consistent with a growing body of evidence for the relationship between depression and subsequent PD, [4][5][6][7][8][9][10][11][12][13][14] and the present study contributes to this evidence with strong, prospective, long-term data. One recent study 13 reported a similar, significant association over a 10-year period, but investigations covering more than a decade of follow-up are rare Table 3 Risk of PD in relation to estimated severity and recurrence of depression, assessed by binary logistic regression and results have been inconclusive.…”
Section: Resultssupporting
confidence: 92%
“…The relationship between depression and subsequent PD appears to be strongest in the few years preceding the onset of motor symptoms, [11][12][13] but it may exist earlier. 5,12,13 Few studies have investigated temporal perspectives of .10 years, and long-term findings have been inconclusive.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…[6][7][8][9] More frequent NMS more than 10 DaT imaging (DaTscan) is used to detect nigrostriatal degeneration; if combined with multiple factors (hyposmia, male sex, and constipation), the probability of detecting subjects with a nigrostriatal deficit increases up to 40%.…”
Section: Introductionmentioning
confidence: 99%